Thinking Creatively About the Data Skills Gap: How Online Training Events Are Supporting SHAPE Higher Education Students - Vanessa Higgins; Jackie Carter (Journal of Statistics and Data Science Education)
There is international demand for data skills in the workplace and evidence that SHAPE (Social Science, Humanities and the Arts for People and the Economy) students can help to fill this gap. This research explores which data skills higher education SHAPE students develop through attendance at UK Data Service online training events. Semi-structured qualitative individual interviews were conducted with 10 SHAPE students who attended UK Data Service online training events; data were analyzed in NVIVO 12 Plus, using reflexive thematic analysis. The results show that, for the SHAPE students who took part in the study, the UK Data Service online data skills training events supported the development of their data skills. The events provided the students with practical applied data skills and skills around planning/designing research and assessing data sources. The events also provided the students with softer skills such as gaining confidence to get started with data, further learning opportunities and access to research communities. The participating students lacked clarity in terms of the skills that they needed to use data and, therefore, a data skills framework to be inclusive of SHAPE students is required to add to the supply of data skills from STEM backgrounds.